2013
DOI: 10.1161/hypertensionaha.111.00566
|View full text |Cite
|
Sign up to set email alerts
|

23 Na Magnetic Resonance Imaging-Determined Tissue Sodium in Healthy Subjects and Hypertensive Patients

Abstract: Dietary salt intake has been investigated in relation to hypertension since the early 20th century.1 Mendelian forms of hypertension have underscored the role of salt intake in the development of hypertension.2 Clinicians have advised patients in terms of their dietary intake and have relied on 24 hour urine collections to verify dietary compliance. 3 Nonetheless, the results have been suboptimal. Clinicians have been limited to measuring Na + in plasma and urine, and the relationship to these sources for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
387
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 346 publications
(422 citation statements)
references
References 18 publications
21
387
2
5
Order By: Relevance
“…Not only patients with refractory hypertension have an increased tissue Na + which is detectable by 23 Na‐NMR (Kopp et al. 2013), but also dystrophic muscle fibers are characterized by an extensive imbalance in the sodium homeostasis (Weber et al. 2012; Jakob et al.…”
Section: Discussionmentioning
confidence: 99%
“…Not only patients with refractory hypertension have an increased tissue Na + which is detectable by 23 Na‐NMR (Kopp et al. 2013), but also dystrophic muscle fibers are characterized by an extensive imbalance in the sodium homeostasis (Weber et al. 2012; Jakob et al.…”
Section: Discussionmentioning
confidence: 99%
“…16 The capacity for nonosmotic sodium storage has been shown for various tissues, such as skin, cartilage, bone, and muscle. 14,[17][18][19][20] Studies using 23 Na magnetic resonance imaging and conventional 1 H magnetic resonance imaging have revealed that, in both patients with primary hyperaldosteronism and patients with essential hypertension, considerable amounts of sodium are stored in muscle and skin without commensurate water retention. 19,20 Experiments in both mice and rats have identified that GAGs in the skin interstitium are responsible for sodium storage.…”
Section: Nonosmotic Sodium Storagementioning
confidence: 99%
“…We have developed 23 Na-MRI as a method to non-invasively study the Na + skin depot in normal and hypertensive humans (12,13). We calibrated the method with human tissue that was then ashed and measured with atomic absorption spectrometry (12).…”
Section: Introductionmentioning
confidence: 99%
“…We calibrated the method with human tissue that was then ashed and measured with atomic absorption spectrometry (12). We have shown that the proposed 3.0 T approach has clinical utility (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%